The Role of Islamic Religious Education in the Implementation of Drug Rehabilitation: Study at the Saung Kawani Rehabilitation Institute, Grapiks Foundation - Rizal Muzahidin; Rizal Kailani; Rizkiyah Fitri Awaliyah (al-Afkar, Journal For Islamic Studies, 2025)
This research was conducted to determine, first, the purpose of Islamic religious education for drug rehabilitation patients in Saung Kawani. The second is the process of Islamic Religious Education for drug rehabilitation patients at Saung Kawani, Grapiks Foundation. These three factors influence the implementation of Islamic Religious Education for drug rehabilitation patients in Saung Kawani. It is known that through education it can be a process of self-discovery as a human being who has the responsibility to build self-confidence, especially patients so that they can rise from adversity and return to the teachings of their religion, especially in Islam. This study used a qualitative method, with a descriptive-analytical approach that revealed the process of Islamic Religious Education for drug rehabilitation patients at the Saung Kawani Grapiks Foundation, and for data analysis using data reduction, data presentation and inference. Data collection techniques and tools used by researchers include interviews, observation and documentation. The results of the study were that: first, the aim of Islamic Religious Education for drug rehabilitation patients is for the patient to become a true Muslim, do good deeds and have good morals so that they can coexist with their community. The two forms of implementation of Islamic values ​​in the rehabilitation process include intention, repentance, prayer, effort, tawakal of gratitude and istiqmah. Third, the factors that influence are divided into two, namely: supporting factors, namely adequate financial sources of funds, support from the local community and creative teachers. As well as inhibiting factors, namely: residents who do not have a strong desire to recover, are still lacking in religious knowledge, and have a poor attitude, very limited facilities and infrastructure.